Odpowiedzi

2009-11-10T10:23:23+01:00
X+y²-8=0
x+y=0
x=-y podstawiamy do pierwszego
-y+y²-8=0
obliczamy Δ
Δ=b²-4ac
Δ=(-1)²-4*1*(-8)=33 √Δ=1+32=√33
x₁=-b-√Δ/2a
x₁=1-√33/2


X₂=-B+√Δ/2A
X₂=1+√33/2 CZYLI MAMY x₁=1-√33/2 x₂=1+√33/2
1 1 1
2009-11-10T10:25:30+01:00
X+y²-8=o
x+y=0

x+y²-8=0
x=-y

-y+y²-8=0
y²-y-8=0
Δ=1-4×1×(-8)=33

y₁=(1-√33)/2
y₂=(1+√33)/2

x₁=-((1-√33)/2)
x₂=-((1+√33)/2)
1 5 1
2009-11-10T10:30:45+01:00
X+y²-8=o
x+y=0 - x=-y
teraz podstawiasz do pierwszego
-y+y²-8=0
y²-y-8=0
z tego liczysz Δ=b²-4ac
Δ=(-1)²-4*1*(-8)=33
√Δ=√33
y=(1-√33)/2
y=(1+√33)2
x=(-1+√33)2
x=(-1-√33)/2
powinno być chyba dobrze
1 1 1